Extending unified theory of acceptance and use of technology to understand the acceptance of digital textbook for elementary School in Indonesia - Hermita, Neni; Wijaya, Tommy Tanu; Yusron, Eri; Abidin, Yunus; Alim, Jesi Alexander; Putra, Zetra Hainul (Frontiers in Education, 2023)
The rapid development of technology has led to the change of textbooks from printed to digital forms accessible by students irrespective of their location, thereby improving their overall academic performance. This change is appropriate to the sustainable learning program, where digital textbooks support online learning and students can access material from anywhere and at any time. This research aims to analyze the factors affecting the intention of elementary school teachers to use digital textbooks. Quantitative data were collected and measured from 493 elementary school teachers in Riau, Indonesia, and analyzed using structural equation modeling (SEM). The results showed that performance expectancy (PE), Effort Expectancy (EE), Social Influence (SI), Perceived learning opportunities (PLO), Self-efficacy (SE) and Facilitating Condition (FC) positively affected teachers' intention to use digital textbooks. SI was found to be the factor with the greatest effect on BI. However, attitude, affective need (AN), ICT usage habits, gender, age, and education level did not affect teachers' intention to use digital textbooks. This research provides important information for the government, decision-makers, and schools on using digital textbooks at the elementary level in the future.